Analysis of the role of the Shc and Grb2 proteins in signal transduction by the v-ErbB protein. - Meyer, S (1994)
The epidermal growth factor receptor, EGFR, has been implicated in cell transformation in both mammalian and avian species. The v-ErbB oncoprotein is an oncogenic form of the chicken EGFR. The tyrosine kinase activity of this oncoprotein is required for transformation, but no transformation-specific cellular substrates have been described to date. Recently activation of the ras signal transduction pathway by the EGFR has been shown to involve the Shc and Grb2 proteins. In this communication, we demonstrate that the Shc proteins are phosphorylated on tyrosine residues and are complexed with Grb2 and the chicken EGFR following ligand activation of this receptor. In fibroblasts and erythroid cells transformed by the avian erythroblastosis virus (AEV) strains H and ES4, the Shc proteins are found to be constitutively phosphorylated on tyrosine residues. The tyrosine-phosphorylated forms of the AEV strain H v-ErbB protein are found in a complex with Shc and Grb2, but the Shc proteins do not bind to the AEV strain ES4 v-ErbB protein. Mutant forms of the v-ErbB protein (in which several of the tyrosines that become autophosphorylated have been deleted by truncation) are unable to transform erythroid cells but can still transform fibroblasts. Analysis of cells transformed by one of these mutants revealed that the truncated v-ErbB protein could no longer bind to either Shc or Grb2, but this oncoprotein still gave rise to tyrosine-phosphorylated Shc proteins that complexed with Grb2 and led to activation of mitogen-activated protein (MAP) kinase. The results suggest that stable binding of Grb2 and Shc to the v-ErbB protein is not necessary to activate this signal transduction pathway and assuming that the mutant activate MAP kinase in erythroid cells in a manner similar to that of fibroblasts, that activation of this pathway is not sufficient to transform erythroid cells.